2015
DOI: 10.1177/0269216315596459
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress symptoms in palliative care professionals seeking mindfulness training: Prevalence and vulnerability

Abstract: Posttraumatic stress disorder symptoms may be common among professionals working in palliative medicine. Professionals prone to avoidant coping and those with more rigid negative thought processes may be at higher risk for posttraumatic stress disorder symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 20 publications
2
32
0
1
Order By: Relevance
“…However, relying solely on self-protection strategies can also strain well-being over the long-term [11, 12]. In fact, a recent study investigating the prevalence of posttraumatic stress disorder symptoms, depression and coping revealed that practitioners who are prone to avoidant coping strategies may have a higher risk for developing posttraumatic stress disorder symptoms [13]. …”
Section: Introductionmentioning
confidence: 99%
“…However, relying solely on self-protection strategies can also strain well-being over the long-term [11, 12]. In fact, a recent study investigating the prevalence of posttraumatic stress disorder symptoms, depression and coping revealed that practitioners who are prone to avoidant coping strategies may have a higher risk for developing posttraumatic stress disorder symptoms [13]. …”
Section: Introductionmentioning
confidence: 99%
“…Mindfulness training for nurses also enhances positive cognitive retraining (Luberto et al, ), an outcome that has been corroborated by studies of brain images, which have shown that mindfulness training produces increases in brain activity, associated with positive moods and the regulation of emotions (Guillaumie, Boiral, & Champagne, ; Huang et al, ; Young et al, ). Some researchers have even observed improvements in reactions to posttraumatic situations (Meyer et al, ; O'Mahony, Gerhart, Grosse, Abrams, & Levy, ) and even positive effects on stress biomarkers such as reduction in cortisol salivary cortisol levels (Veiga et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings converge with other studies documenting similar rates of PTSD in health care professionals. 1,14 More work is needed to clarify the predictors, presentation, and consequences of PTSD in pediatric oncology professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Professionals providing medical care to children with cancer may derive a sense of meaning and purpose in their work. However, frequent exposure to patient trauma and mortality may elicit symptoms of posttraumatic stress disorder (PTSD) . PTSD is conceptualized to arise in response to life‐threatening events that threaten core beliefs and expectations, including through the repeated witnessing or hearing of others' trauma as part of one's professional role .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation